2019
DOI: 10.2106/jbjs.18.00773
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Mobilization After Superior Rotator Cuff Repair: Sling Versus No Sling

Abstract: Background: Patients are commonly advised to wear a sling for 4 to 6 weeks after rotator cuff repair despite negative effects of early immobilization and benefits of motion rehabilitation. The aim of this study was to compare clinical and radiographic outcomes up to 6 months following rotator cuff repair with and without postoperative sling immobilization. Methods: We randomized 80 patients scheduled for arthroscopic repair of a small or medium superior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
39
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(42 citation statements)
references
References 58 publications
0
39
0
3
Order By: Relevance
“…Other recent randomised controlled trials have been reported. 11 , 20 , 21 Mazzocca et al 20 ( n = 73) compared early movement (starting two to three days after surgery) versus delayed movement (starting 28 days after surgery), similar to standard rehabilitation reported here. There was no statistically significant difference in Western Ontario Rotator Cuff scores at six months, but the early movement group reported lower scores (better clinical status) throughout the post-operative period.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Other recent randomised controlled trials have been reported. 11 , 20 , 21 Mazzocca et al 20 ( n = 73) compared early movement (starting two to three days after surgery) versus delayed movement (starting 28 days after surgery), similar to standard rehabilitation reported here. There was no statistically significant difference in Western Ontario Rotator Cuff scores at six months, but the early movement group reported lower scores (better clinical status) throughout the post-operative period.…”
Section: Discussionmentioning
confidence: 94%
“…After one year there was no difference in re-tear rates (30% vs 33%) and after two years there was no difference in clinical outcomes. Tirefort et al 21 ( n = 80) compared no sling versus the use of a sling for the first four post-operative weeks following arthroscopic rotator cuff repair (small to medium tears included). There was a statistically significant improvement in range of movement at six and 12 weeks for the no sling group.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical tension and anxiety about compromising the surgical repair with early patient-directed rehabilitation was apparent. Recent international randomised controlled trials have reported similar re-tear rates in early versus delayed mobilisation groups, 12 , 13 but were not powered to detect a difference in re-tear rates between groups. To enable a valid comparison in a future randomised controlled trial this tension needs to be recognised and pro-actively discussed with the aim of working with clinicians in equipoise.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to address the debate of the importance of sling wear postoperatively for rotator cuff tears. Tirefort et al [ 17 ] recently showed no difference in outcomes when comparing sling immobilization versus no restrictions postoperatively for small-to-medium sized tears. Compliance with sling immobilization was self-reported, however, and may not reflect actual sling wear.…”
Section: Discussionmentioning
confidence: 99%